1997
DOI: 10.1111/j.1349-7006.1997.tb00319.x
|View full text |Cite
|
Sign up to set email alerts
|

All‐trans‐retinoic Acid‐dependent Inhibition of E‐Cadherin‐based Cell Adhesion with Concomitant Dephosphorylation of β‐Catenin in Metastatic Human Renal Carcinoma Cells

Abstract: We previously described an in vitro invasion assay model, using a monolayer of vascular endothelial cells grown on collagen gel, that mimics the metastatic abilities of the highly metastatic human renal carcinoma cell lines, MM‐1,3 and 8 and their poorly metastatic counterparts, SN12C and Q‐8. MM‐1, 3 and 8 cells were observed to penetrate the monolayer of vascular endothelial cells and grew in a spreading or scattering manner with loose cell‐cell contact on collagen gel or on vascular endothelial cells. SN12C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…1 ). These two cell types were chosen as controls in view of the previously described hormone interference with AP‐1 activation [31]. In contrast, VDR RNA expression was only relevant in HMEC‐1 cells while it was undetectable in EOMA and MS‐1 lines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ). These two cell types were chosen as controls in view of the previously described hormone interference with AP‐1 activation [31]. In contrast, VDR RNA expression was only relevant in HMEC‐1 cells while it was undetectable in EOMA and MS‐1 lines.…”
Section: Resultsmentioning
confidence: 99%
“…The tissue‐ and urokinase‐type plasminogen activator proteases are regulated by RA [9,23–25]. Glucocorticoids, RA, and vitD3 also regulate the expression of several adhesion molecules that may contribute to the angiogenic process: intracellular adhesion molecule‐1 [26], vascular cellular adhesion molecule‐1 [27], E‐selectin [28], L‐selectin [29], tenascin [30], and E‐cadherin [31]. In most cases expression of these molecules is repressed by hormone‐bound nuclear receptors.…”
Section: Introductionmentioning
confidence: 99%
“…The inverse correlation between ALDH1A2 and vimentin expression in tumor cells was further supported in a mouse xenograft model in vivo and tumor sections from OPSCC patients. Although, the underlying molecular mechanism remains to be elucidated, several studies reported that ATRA inhibits tumor cell invasion and metastatic potential in diverse model systems by modulating cell-to-cell adhesion and RAR-dependent regulation of proteins implicated in epithelial-to-mesenchymal transition [ 22 25 ]. It is also worth noting that a continuous cultivation of FaDu cells in the presence of WIN18.446 or BMS493, respectively, results in formation of stable and expandable tumorspheres, suggesting that tumor cells lacking ALDH1A2-RAR signaling also gain the capacity to avoid anoikis and acquire stem cell traits (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…While there is evidence that RA alters the cadherin‐catenin pathways in cell culture (Jonk et al. 1994; Ryuto et al. 1997; Shah et al.…”
Section: Introductionmentioning
confidence: 99%